Behavioral competence: how host behaviors can interact to influence parasite transmission risk. (December 2015) - Barron, DG; Gervasi, SS; Pruitt, JN; Martin, LB
Highlights: Behavioral defenses decrease risk of contracting and spreading parasites. The cumulative expression of multiple anti-parasite behaviors determines risk. Behavioral profiles can be plastic with regard to environment or infection status. Behavioral and immunological systems are tightly linked. Abstract : Hosts vary in their ability to transmit new parasite infections (i.e. competence). Although behavior is suggested as a source of individual-level variation, the contribution of host behavior to host–parasite dynamics at the population-level remains largely enigmatic. Here we advocate that behavioral competence be characterized as a syndrome of behaviors that interact to directly or indirectly influence transmission potential. These behaviors can be plastic in response to environmental conditions and/or infection state, and appear linked to immunological traits through shared physiological regulation. By integrating behavioral variation and covariation into a whole-organism view of host competence, disease ecologists might more realistically characterize an individual's role in host–parasite systems.